2013
DOI: 10.1186/1746-6148-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cortisol and faecal cortisol metabolites concentrations in stereotypic and non-stereotypic horses: do stereotypic horses cope better with poor environmental conditions?

Abstract: BackgroundStereotypic behaviours, i.e. repetitive behaviours induced by frustration, repeated attempts to cope and/or brain dysfunction, are intriguing as they occur in a variety of domestic and captive species without any clear adaptive function. Among the different hypotheses, the coping hypothesis predicts that stereotypic behaviours provide a way for animals in unfavourable environmental conditions to adjust. As such, they are expected to have a lower physiological stress level (glucocorticoids) than non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 44 publications
6
33
0
8
Order By: Relevance
“…Crib-biting horses may therefore not be capable to react as efficiently as other horses to an external stimulus, suggesting that crib-biters are more stress-sensitive and less flexible when coping with stress [7]. By contrast, and in accordance with our results, other studies did not find any significant difference in the mean HR or in the HR variability between crib-biters and other horses [18,30,47,48].…”
Section: Sam Axis Response Of Crib-biters and Controlssupporting
confidence: 85%
“…Crib-biting horses may therefore not be capable to react as efficiently as other horses to an external stimulus, suggesting that crib-biters are more stress-sensitive and less flexible when coping with stress [7]. By contrast, and in accordance with our results, other studies did not find any significant difference in the mean HR or in the HR variability between crib-biters and other horses [18,30,47,48].…”
Section: Sam Axis Response Of Crib-biters and Controlssupporting
confidence: 85%
“…valencia era de entre 0,31% y 1% (Muñoz et al, 2009;Tadich et al, 2012). Sin embargo, esta baja prevalencia llama la atención, ya que en caballos FSC la prevalencia de balanceo varía entre 2,15 y 2,94% (Tadich et al, 2013;Muñoz et al, 2014) y en caballos árabes es mayor a 15% (Benhajali et al, 2010;Fureix et al, 2013). Por lo que se puede inferir que podría haber factores hereditarios y/o de manejo que hacen que esta estereotipia sea de tan baja presentación en el caballo chileno.…”
Section: Discussionunclassified
“…Ninguna de estas conductas ha sido observada en caballos de vida libre (Hosthersall y Nicol, 2009;McGreevy, 2012). Entre los factores de riesgo intrínsecos están la raza, edad y sexo (Sarrafchi y Blokhuis, 2013), y entre las consecuencias asociadas a las estereotipias clásicas están algunos problemas de salud tales como atrapamiento de intestino en el foramen epiploico (Archer et al, 2008), osteoartropatía temporohioidal (Grenager et al, 2010), cólico recurrente (Malamed et al, 2010), disminución de la fertilidad (Benhajali et al, 2014), y disminución del peso o de la condición corporal (Houpt, 2005;McGreevy, 2012), por lo tanto la presencia de estas estereotipias hacen que el valor comercial de los caballos afectados disminuya (McGreevy, 2011).…”
Section: Introductionunclassified
“…The total prevalence of both stereotypies found in tiestall stabled horses, although it is within the wide range from 0 to 59.2% described by other authors, is one of the lowest reported in the literature (9,11,17,(20)(21)(22)24,(27)(28)(29)32,33,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Notoriously, the total prevalence is close to the 4.2% reported by Pagliosa et al (33) in a study conducted in 72 military horses kept in tie stalls, including that weaving in both studies does not exceed 1.4%.…”
Section: Discussionmentioning
confidence: 50%